Pembuatan Biodiesel Dari Minyak Nyamplung Dengan Katalis Na2SiO3/Serbuk Besi : Pengaruh Kecepatan Pengadukan Dan Recycle Katalis - Febrian Adhitya; Edy Saputra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research purpose to synthesis biodiesel from calophyllum inophyllum oil by transesterification reaction using heterogeneous base catalyst Na2SiO3/iron powder. Catalyst was synthesized from fly ash palm oil which supported by iron powder. Synthesis biodiesel on transesterification reaction with the independent variables of this research variations is agitation rate of 200 rpm, 300 rpm and 400 rpm and catalyst can be recycledas much as 3 times for every variation of agitation rate. These conditions aim to determine its effect on the yield of biodiesel produced. Condition operation the transesterification are mol ratio of oil : methanol 1 : 9 and loading catalyst 3%-w of oil feedstock with temperature reaction 60°C during 2 hours reaction time. Physical characterization were done such as density 867 kg/m3, kinematic viscosity 3,96 mm2/s, acid number 0,48 mg-KOH/g biodiesel and flash point 147°C respectively accordance with the Indonesian National Standard. (SNI 7182:2015).Keyword: Agitation Rate, Biodiesel, Esterification, Calophyllum inophyllum oil, Catalyst, Recyle and Transesterification.